Ladybird Dictionaru - LadyBird (London Ladybird, 2018)
Ladybird Dictionary will help young learners aged 4-11 to find and understand words in English. This engaging dictionary is informed by the Cambridge Young Learners wordlists, and features an introduction on how to use the dictionary, an a-z section, and a picture dictionary at the back, which groups words that are useful to learn together.